Casting Activity of Scherotheca gigas in No-Till Mediterranean Soils: Role in Organic Matter Incorporation and Influence of Aridity - Paloma Bescansa; Iñigo Virto; Oihane Fernández-Ugalde; María José Imaz; Alberto Enrique (Applied and Environmental Soil Science)
The behaviour of earthworms, their role in organic matter incorporation into the soil, and the influence of aridity in such processes in arid and semiarid regions have scarcely been studied. In this study, physico-chemical analyses of the casts and the surrounding no-till agricultural soils of three experimental sites representing an aridity gradient in Navarre (NW Spain) were done. The casts were formed by the activity of the only anecic species, Scherotheca gigas (Dugès, 1828), ubiquitous in no-till soils in this region. We observed a significant depletion of clay and higher concentration of total organic C and labile C in the form of particulate organic matter (POM) in the casts as compared to the surrounding soil, suggesting selective ingestion of soil by S. gigas. This, together with the observation of increased concentration in POM with increasing aridity, suggests a major role of this species in the observed progressive gains of organic C stocks in no-till soils in the region.